Increased Risk of Depression Recurrence after Initiation of Prescription Opioids in Non-Cancer Pain Patients - Scherrer, Jeffrey F. (J Pain, 2016)
Several studies have demonstrated chronic opioid analgesic use is associated with increased risk of new onset depression. It is not known if patients with remitted depression are at increased risk of relapse following exposure to opioid analgesics. A retrospective cohort design using patient data from the Veterans Health Administration (VHA; n=5,400), and Baylor Scott & White Health (BSWH; n=842) was performed with an observation period 2002–2012 in VHA and 2003–2012 in BSWH. Eligible patients had a diagnosis of depression at baseline and experienced a period of remission. Risk of depression recurrence was modeled in patients that either started an opioid or remained without opioid prescriptions before or during remission. Cox-proportional hazard models measured the association between opioid use and depression recurrence controlling for pain, and other confounders. Patients exposed to an opioid compared to those unexposed had a significantly greater risk of depression recurrence in both patient populations (VHA: HR=2.17; 95% CI:2.01–2.34; BSWH: HR=1.77; 95% CI:1.42–2.21). These results suggest opioid use doubles the risk of depression recurrence even after controlling for pain, psychiatric disorders and opioid misuse. Further work is needed to determine if risk increases with duration of use. Repeated screening for depression after opioid initiation may be warranted.